PENDAMPINGAN TEKNOLOGI DESTILASI MINYAK KAYU PUTIH UNTUK MENINGKATKAN PRODUKSI MINYAK KAYU PUTIH KELOMPOK TANI FAOT BANO - Jefrianus Nino; Yakobus Pffeferius Edvent Saba Agu; Aloisius Loka Son; Handrianus Mentu; I Ketut Sumantar; I Ketut Widnyana; Sekar Wangi (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
Maubesi Village is an area with significant potential for the development of eucalyptus (Melaleuca cajuputi). The Faot Bano Farmers Group utilizes this plant through distillation using a simple distillation apparatus made from a rust-proof drum, with an ineffective cooling system, resulting in low eucalyptus oil yield. Recognizing this potential, a eucalyptus oil distillation technology mentoring program was conducted to improve farmers' technical capacity in the production process and to improve the yield and quality of the eucalyptus oil produced. The program methods included knowledge transfer, distillation equipment operational training, and hands-on distillation practice using appropriate and easy-to-operate distillation equipment. The distillation process, which takes 4-5 hours, produces an oil yield of 1.5 liters (1.5%) from 100 kg of eucalyptus leaves. The oil yield increased compared to before the mentoring program, and the oil quality met better visual and aromatic characteristics. This activity proves that the application of appropriate distillation technology and supported by continuous mentoring can increase the production and quality of eucalyptus oil, and has the potential to strengthen the economic independence of the Maubesi Village community based on local resources.